MENGIMPLEMENTASIKAN LITERASI PERPUSTKAAAN DI LINGKUNGAN AKADEMIK STKIP PGRI SUMENEP - Nina Karina; Ananda Rizky Amelia (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Library literacy is defined as the ability to access, evaluate, and utilize information effectively through the use of library services. In the context of the academic environment of STKIP (Teacher Training College and Education), this study aims to describe various forms of library literacy implementation, the role of librarians, the technological support provided, and the challenges faced in the implementation process. The research method used is a literature review with a library study approach and limited field observations. The results of the analysis show that library literacy has been implemented through user orientation activities, scientific information access training, and digital technology integration. However, obstacles such as low levels of student participation, limited facilities available, and lack of collaboration between stakeholders are still major challenges. Therefore, synergy is needed between the library, lecturers, and institutional leaders to increase the effectiveness of information literacy as an essential component in the educational process at STKIP